Risk Factors Affecting Cognitive Impairment of the Elderly Aged 65 and Over: A Cross-Sectional Study - Han, Fengyue; Luo, Changjiang; Lv, Duojiao; Tian, Long; Qu, Chuanqiang (Frontiers in Aging Neuroscience, 2022)
Objectives: Elderly population with cognitive impairment has been accelerating in China. This study aimed to explore the relationship between each risk factor and each cognitive domain to provide evidence for risk prevention of controlling impaired cognitive function in elderly. Methods: This cross-sectional study analyzed the cognitive status of the elderly aged 65 and above in three communities in Shizhong District of Jinan City. Cognitive status was assessed by MMSE. The influencing factors of cognitive impairment were analyzed by chi square test, correlation analysis and regression analysis. Results: Among 1171 participants, 643 were defined as cognitive impairment with an incidence of 54.9%. And we found that there were significant differences in the incidence of cognitive impairment among residents with different gender, age, education level, hypertension and LDL-C (P < 0.05). However, BMI, marital status, smoking, physical exercise, T2DM, TC, TG and HDL-C had no significant differences in the incidence of cognitive impairment. In addition, education level (b = 1.194, P <. 001), age (b = -0.040, P = 0.001), LDL-C (b = 0.169, P = 0.018) had statistical significance on the total score of MMSE according to binary logistic regression analysis. Conclusions: Gender, age, education level, hypertension and LDL-C had significant differences in the incidence of cognitive impairment. And these risk factors could provide a basis for the early screening and intervention of cognitive impairment in the elderly.